THE INFLUENCE OF VIRAL MARKETING AND INFLUENCER MARKETING AGAINST PURCHASE INTENTION TIKTOK ACCOUNT @Somethincofficial - fransiska perintis br lumban gaol (Indonesian Journal of Digital Business, 2023)
The purpose of this study is to ascertain how viral marketing and influencer marketing on TikTok influence consumers' intent to purchase Somethinc items. Data for this study were gathered quantitatively utilizing survey methods. A survey distributed via Google Form served as the research tool. In this study, 414 respondents who followed @somethincofficial on TikTok served as samples. Multiple linear analysis and descriptive analysis are the analysis methods employed. The findings of this study indicate that influencer marketing has an impact on purchase intention on TikTok accounts @somethincofficial whereas viral marketing has an impact on those accounts.  Influencer marketing and viral marketing both influence future purchases. Based on the findings of the ability of independent variables to determine the coefficient of determination (viral marketing), The independent variable (and influencer marketing) in this study affects the dependent variable by 54%, while other variables in the study account for the remaining 46% (1 - 0.540).